Robotization and labor supply in the context of a dynamic monopsony: novel evidence from South Korea - Saade, Ahmed J.; Alexiou, Constantinos; Belghitar, Yacine (Institute of Economic Research (Korea) et al., 2022)
We estimate the effects of robotization on labor supply in Manufacturing, Services and the whole of the South Korean economy using exponential hazard and a random effects logit methodologies over the period 1999-2019. Our findings suggest that a larger operational stock of industrial robots in manufacturing is associated with manufacturing (non-manufacturing) workers becoming more (less) responsive to a change in wages in their decision to quit to non-employment, whilst the ease with which firms can poach workers is found to be unaffected by robotization.
Keywords: Automation; Dynamic monopsony; Elasticity of labor supply; Industrial robots; Labor share; South Korea